Tidally Induced Magmatic Pulses on the Oceanic Floor of Jupiter's Moon Europa. Issue 3 (2nd February 2021) - Běhounková, Marie; Tobie, Gabriel; Choblet, Gaël; Kervazo, Mathilde; Melwani Daswani, Mohit; Dumoulin, Caroline; Vance, Steven D.
Abstract: The habitability of Europa's subsurface ocean is conditioned by heat released from the deep interior and by intensity of magmatic activity. Here, we investigate the melting of the silicate mantle through time and its consequences for seafloor magmatism by modeling Europa's internal heat production and transfer using a three‐dimensional numerical model. We show that melt can be produced during most of Europa's history due to the limited efficiency of internal cooling by thermal convection and the presence of radiogenic heating. The melting rate is amplified by tidal friction, possibly leading to magmatic pulses during enhanced eccentricity periods and focusing melting to high latitudes. The volume of generated melts during magmatic episodes is comparable to those involved in Large Igneous Provinces, commonly observed on Earth, and may impact ocean chemistry. We predict that gravity measurements, detection of anomalous H2 /CH4, and astrometric data by future missions could confirm ongoing large‐scale seafloor activity. Plain Language Summary: Jupiter's icy moon Europa harbors underneath a tectonically modified ice shell a salty ocean in direct contact with a rocky interior. Such an oceanic environment makes Europa a primary target for the search of a habitable world outside the Earth. The occurrence of magmatic activity on the seafloor is essential to determine if it constitutes an environment hospitable to life. Using a three‐dimensional numerical model, we demonstrate that the magmatic activity can continue during most of Europa's history even though it progressively decays as the interior cools down. We predict that magmatic activity should be modulated in time due to change in the moon's orbit, and should focus in polar regions where the heat produced by tidal friction is the largest. The predicted magmatic pulses should be accompanied by the release of volatiles that may impact the oceanic chemistry and may be detected by upcoming spacecraft missions. Key Points: The melting of Europa's mantle is investigated by three‐dimensional modeling of heat production and transfer Magmatic activity can persist up to the present at high latitudes where tidal heating is maximal Measurements by upcoming missions are identified that might confirm ongoing volcanic activity